Parasite-Specific Immunomodulatory Functions of Filarial Cystatin - Schierack, Peter (American Society for Microbiology, 2003)
Cystatins of parasitic nematodes are well-described pathogenicity factors which contribute to downregulation of T-cell proliferation of their hosts and induce anti-inflammatory cytokine responses. We compared the immunomodulatory effects of two cystatins of the filarial nematodes Onchocerca volvulus and Acanthocheilonema viteae with two homologous proteins of the free-living nematode Caenorhabditis elegans. Like filarial cystatins, the C. elegans cystatins (rCysele1 and rCysele2) possessed domains relevant for inhibition of papain-like proteases and were biologically active inhibitors of human cathepsins B, L, and S. However, the inhibition of cathepsin B by C. elegans cystatin was much stronger. C. elegans cystatins lacked a domain involved in inhibition of legumain-like proteases that was present in O. volvulus cystatin. Filarial cystatins suppressed the proliferation of human peripheral blood mononuclear cells (PBMC) and murine spleen cells, while the C. elegans cystatins had this effect to a much lesser extent. Whereas filarial cystatins markedly increased the production of interleukin (IL)-10, C. elegans cystatins increased the production of IL-12 and gamma interferon (IFN-γ) by human PBMC. The cystatins of both the filariae and C. elegans induced an upregulation of inducible nitric oxide by IFN-γ-stimulated murine macrophages. These data suggest that filarial cystatins but not the C. elegans cystatins downregulate proliferative responses of host cells due to characteristics which might reflect an adaptation of filariae to their parasitic life style.